CREATING A HIGHLY EFFICIENT PROJECT TEAM AS A PLEDGE OF SUCCESS - K.E. Mendigaliev; Tsekhovoy A.F (Academic Journal of Physical and Chemical Sciences, 2019)
In the conditions of existing competition in the market of innovative products, the requirements for personnel entrusted with the development of a new product or other type of activity are increasing. The need to have effective workers is dictated by the need to first bring a new product to the market, whereby the team working on a specific task must work efficiently, without loss of time. As a result, the question arises, how can a highly efficient team be formed? The article discusses the methods for determining the team interaction model, which in turn is the foundation for building an effective work of the project team. The authors considered the algorithm of using tools and methods of development of the project team, depending on the scale of the projects, which can contribute to the effective interaction of team members. Correct and competent formation of the team relationship with the definition of areas of responsibility contributes to the creation of an effective system of motivation and incentives for company employees - this is, to a greater extent, the key to successful implementation of any project ..